Karakterisasi Material Penyimpan Kalor Laten Menggunakan Metode T-History - Ully Muzakir; - Hamdani; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2012)
The capacity of energy storage and temperature storage has come into consideration in choosing thermal energy storage system. Absorbed or released material either big or small can be determined by finding the value of the specific heat (Cp) and the latent heat fusion (HL). Available method to determine latent heat of fusion (H), specific heat (Cp), temperature melting (Tm) and thermal conductivity (k) are conventional calorimetry method, Differential Thermal Analysis (DTA) and Differential Scanning Calorimetry (DSC). Measurement of physical properties of phase change material using DTA and DSC has disadvantage due to small weight that used for sample (1-10 mg), so that thermophysic of sample usually different when the material is used in large quantities. In this study, T-history method is used to determine thermophysic heat storage material. Examination results show the match value in latent heat (Hm) of paraffin with DSC testing results are 249.42 KJ / kg with 251 KJ / kg. The results of calculations using the T-History for paraffin obtained at temperature Tm 52.72 to 59.9 0C; Cp of 2.54 to 3.57 KJ / Kg.K; Hm at 249.42 KJ / Kg; k of 0, 18 W / mK. For bee-wax Tm obtained at temperatures from 52.4 to 61.79 0C; Cp of 2.65 to 3.45 KJ / Kg.K; Hm of 171 KJ / Kg; k of 0.234 W / mK. For fat cow obtained at temperature Tm 40.82 to 44.10C; Cp of 3.19 to 4.16 KJ / Kg.K; Hm at 60.13 KJ / Kg; k of 0.181 W / mK. It can be concluded after examanination that Paraffin is a good material as a phase change material (PCM) in comparison to bee-wax and beef fat.